Analysis and Design of Work Systems using Hazard Analysis and Critical Control Points (HACCP) Standards at Mr. Sarbani’s Tempe Jombor Sukoharjo - Lestari, Mathilda Sri; Prasetyo, Rian; Hartanti, Sri (JURNAL Al-AZHAR INDONESIA SERI SAINS DAN TEKNOLOGI, 2023)
MSMEs have very large number of actors so they play an important role in community welfare. One popular type of MSMEs is the food producer. This study focuses on UKM Tempe Pak Sarbani  (UKMTS), who produces tempe, the traditional Indonesian food and is located in Jombor Sukoharjo.  UKMTS production process is directly related to the production environment because it affects the level of productivity, smoothness, and timeliness of production. The tempe production processes at UKMTS are still manual, and have not met the conditions for the application of Good Processed Food Production Methods (CPP). At UKMTS production processes do not yet meet standards and have irregular facility arrangements which greatly hinder operators in carrying out the production process. Therefore it is necessary to improve the work system and design a repair work system based on HACCP principles to  meet HACCP standards for the MSME scale. Based on all the discrepancies observed, currently the application of CPPB for UKMTS is at level 4. At this level, 9 critical control points are indicated which must be made critical, monitored and improved to avoid dangers that may occur. In the last stage of implementing HACCP in UKMTS, a documentation system was created for the monitoring process.Keywords – HACCP, Production, Work System, MSME (UKM).